Realignment of roles, attachment styles in family relationships and reassessment of values of overseas Filipino worker returnees in Tigbauan, Iloilo - Bacero, Mon Ritche Y.; Benosa, Aaron Alden O.
This study was conducted to find out the roles and values change and adjustments in the family relationships undergone by an oversease Filipino Worker (OFW) returnee during his post employment. Thirty (30) OFW returnees from chosen Barangays in Tigbauan participated in answering the Traditional Marital Role Questionnaire, Experience in Close Relationships-Revised (ECR-R) Questionnaire, and an interview guide for the assessment of their Filipino Values and Ideals. Results showed that most of the traditional marital roles are not exclusive anymore to one spouse, rather done by both. Good relationship based on trust was found among majority of the respondents since they are securely-attached to their families. Positive values change in respect became apparent for some OFWs who alleviated the family's situation.
Thesis (Undergraduate, Bachelor of Arts in Psychology)College of Arts and Sciences, University of the Philippines in the Visayas, Miag-ao, Iloilo.
Keywords: Overseas Filipino workers. -- Tigbauan, Iloilo